Auditory Gap Detection, Perceptual Channels, and Temporal Resolution in Speech Perception - Phillips, Dennis P. (Journal of the American Academy of Audiology, 1999)
This article overviews some recent advances in our understanding of temporal processes in auditory perception. It begins with the premise that hearing is the online perceptual elaboration of acoustic events distributed in time. It examines studies of gap detection for two reasons: first, to probe the temporal acuity of auditory perception in its own right and, second, to show how studies of gap detection have provided new insights into the processes involved in speech perception and into the architecture of auditory spatial perceptual mechanisms. The implications of these new data for our comprehension of some central auditory processing disorders are examined.Abbreviations: SLI = specific language impairment, VOT = voice onset time
Keywords: Gap detection; perceptual channels; sound localization; speech perception; temporal resolution